Medieval Nubia: A contribution to the study of textiles from Meinarti - Wozniak, Magdalena M.; Czaja, Barbara (Archaeological Textiles Review, 2020)
An examina􀆟 on of textile finds from Meinarti led to a new identification of pieces of textile, including fragments of furnishing textiles, most likely carpets, previously unnoticed in the assemblage. This new evidence expands the available knowledge about textiles for furniture in medieval Nubia. The article describes the technical features of the fabrics and discusses their potential social and economic value in the archaeological context and during the specific historical period of the site.